Influence of an excitation source on the power indicators of a linear pulse electromechanical converter of induction type - Bolyukh, V. F.; Shchukin, I. S. (Інститут електродинаміки НАН України, 2021)
The purpose of the article is to evaluate the efficiency of an induction-type linear pulse electromechanical converter (LPEC) when operating in shock-power mode and excitation from an alternating voltage source (AVS) in comparison with excitation from a capacitive energy storage (CES). A mathematical model of an induction-type LPEC has been developed both when excited by a unipolar pulse from a CES and from an AVS using lumped parameters of the windings, which takes into account the interrelated electromagnetic, mechanical and thermal processes. It has been found that when the LPEC is excited from the AVS with a voltage frequency of 50 Hz, the electrodynamic force takes on a periodic decaying character with a significant prevalence of positive components of forces over negative ones. The maximum value of the force is much less, and the value of its impulse is much greater than in the LPEC, excited from the CES. With an increase in the frequency of the AVS voltage from 50 to 150 Hz, the highest value of the current density of the inductor winding decreases, and in the armature winding it increases. The greatest values of force and impulse of force are realized at a voltage frequency of 150 Hz. With an increase in the AVS frequency, the relative indicator of the efficiency of the LPEC increases.

Метою статті є оцінка ефективності лінійного імпульсного електромеханічного перетворювача (ЛІЕП) індукційного типу під час роботи в ударно-силовому режимі і збудженні від джерела змінної напруги (ДЗН) в порівнянні зі збудженням від ємнісного накопичувача енергії (ЄНЕ). Розроблено математичну модель ЛІЕП індукційного типу як під час збудження однополярним імпульсом від ЄНЕ, так і від ДЗН з використанням зосереджених параметрів обмоток, яка враховує взаємозалежні електромагнітні, механічні та теплові процеси. Встановлено, що у разі збудження ЛІЕП від ДЗН з частотою напруги 50 Гц електродинамічна сила приймає періодичний загасаючий характер зі значним превалюванням позитивних складових сил над негативними. Максимальна величина сили значно менше, а величина її імпульсу значно більше, ніж в ЛІЕП, який збуджується від ЄНЕ. Зі збільшенням частоти напруги ДЗН від 50 до 150 Гц найбільше значення щільності струму обмотки індуктора зменшується, а в обмотці якоря підвищується. Найбільші величини сили і імпульсу сили реалізуються за частоти напруги 150 Гц. У разі збільшення частоти напруги ДЗН відносний показник ефективності ЛІЕП підвищується.
Вплив джерела збудження на силові показники лінійного імпульсного електромеханічного перетворювача індукційного типу
Keywords: linear pulse electromechanical converter of induction type; mathematical model; alternating voltage source; capacitive energy storage; electromechanical processes and power indicators; лінійний імпульсний електромеханічний перетворювач індукційного типу; математична модель; джерело змінної напруги; ємнісний накопичувач енергії; електромеханічні процеси і силові показники